ANALISA PEMELIHARAAN KOREKTIF TERHADAP INFUS PUMP MINDRAY BENEFUSION VP5 - Khairil Abdillah; Hotromasari Dabukke; Fazri Maulana; Greace Seselia Br Tarigan (JURNAL MUTIARA ELEKTROMEDIK, 2021)
Research has been done on the infusion pump. As for the purpose of this study is to determine the problem of repairing the infusion pump. Corrective maintenance is maintenance action taken to overcome damage or congestion that occurs repeatedl, then take corrective action on teh tool. An infusion pump is a medical device that is used to provide additional electrolytes in the form of a liquid that is injected into the patient’s body in a certain amount through a vein. The display of the infusion pump device does not turn on due ti the disconnection of the flexible cable connector between the LCD and the device’s mother board. During operation a red high sound alarm appears for 10 seconds. When checking the infus pump., it was found that the infusion hose was loose for the patient user, in other checks, the infusion pump clamp was found to be broken. The research is that the infusion pump has been functioning properly after checking and repairing. Maintenance of the infusion pump must be routine and scheduled to prevent damage so that the life of the tool is long. Testing and calibration of the infusion pump, especially on the parameters of the infusion pump, it is mandatory to carry out routine checks on the infusion pump.